1993
DOI: 10.3382/ps.0720636
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Lactose on Cecal Morphology, pH, Organic Acids, and Salmonella enteritidis Organ Invasion in Leghorn Chicks

Abstract: The effect of 14 or 19 days of 10% dietary lactose administration on Salmonella enteritidis (SE) colonization and histological, morphometric, and organic acid changes of the ceca were investigated. At Day 13 or 18, chicks were challenged with 10(8) cfu of SE. Chicks were killed and cultured 24 h later. A reduction in the total number of positive SE organ invasions was observed following 14 days (P < .001) or 19 days (P < .005) of treatment in chicks fed with lactose. Histological examination revealed a marked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…In the present study, the pH of caecal digesta was lower in birds provided diets with inulin and lactose. Also Corrier et al (1991), who provided 2.5% lactose in drinking water, and Tellez et al (1993), who administrated 10% of lactose in feed, reported a lowered pH in the caecal contents of broilers.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, the pH of caecal digesta was lower in birds provided diets with inulin and lactose. Also Corrier et al (1991), who provided 2.5% lactose in drinking water, and Tellez et al (1993), who administrated 10% of lactose in feed, reported a lowered pH in the caecal contents of broilers.…”
Section: Resultsmentioning
confidence: 99%
“…There is some molecular evidence that the cecum supports the growth and colonization of subpopulations of Salmonella that vary in LPS O-chain composition, whereas the intestine favors smooth strains (33). Gut physiology can be manipulated, and many types of biological controls and diets have been designed with the idea of excluding pathogenic salmonellae from the gut (6,24,26,27,30,42,50). Refinement of these approaches to suppress the emergence of subpopulations of S. enterica serovar Enteritidis that have tropism for the reproductive tract of the hen might further reduce the number of contaminated eggs that reach the market.…”
Section: Discussionmentioning
confidence: 99%
“…The results of some studies have shown the ability of chicken gut anaerobic microbiota to convert lactose to short-chain organic acids, especially lactate and propionate (Rehman et al, 2009). A lower pH of the digesta resulting from lactose fermentation may have a positive impact on intestinal histomorphology and/or on the colonization of beneficial microflora in the gastrointestinal tract when administered at both very high (10%) or moderate (2.8%) levels (Tellez et al, 1993;Samli et al, 2007). Conflicting data exist, however, about the effects of dietary lactose on chicken growth performance.…”
Section: Introductionmentioning
confidence: 99%